Multi-elemental ionic liquid-based solvent bar micro-extraction of priority and emerging trace metallic pollutants (Cd, Ag, Pd) in natural waters - Herce-Sesa, Belén; López-López, José A.; Moreno, Carlos (Journal of hazardous materials, 2019)
•Cyphos® 101 solvent bar efficiently extracts Ag, Cd and Pd from saline samples.•Leaching lower than 0.1% was controlled by the use of solvent bar configuration.•Speciation of Ag, Cd and Pd is a key factor for extraction with Cyphos® 101. Transition metals Cd, Pd and Ag are toxic even at very low concentration. Cd is considered a priority substance; while, Pd and Ag are emerging pollutants. Membrane technologies have been applied for their extraction; however, they require important amounts of reagents, time and energy. Additionally, effective reagents for metal extraction in saline natural waters are limited. In this case, hollow fiber liquid phase micro-extraction with a configuration of solvent bar (SBME) using the ionic liquid Cyphos® 101 as extractant is proposed. Optimized conditions for SBME of Cd, Ag and Pd were 50% Cyphos® 101 in the organic solution, extraction time 30 min and 800 rpm stirring rate. Leaching was in all cases lower than 0.1%. Metallic concentrations were measured by flame atomic absorption spectroscopy. The method was applied to the extraction of Ag, Cd and Pd in natural water samples. Except for waste water, Pd extraction was higher than 90% in all cases. Cd (≈100%) and Ag (93–95%) offered their best results for saline samples. Concluding, the proposed system is a low cost and green methodology that allows a simple and fast extraction of trace pollutants such as Ag, Cd and Pd in different natural waters, including highly saline samples.